2001
DOI: 10.1177/070674370104600609
|View full text |Cite
|
Sign up to set email alerts
|

Pre-, Peri-, and Postnatal Trauma in Subjects with Attention-Deficit Hyperactivity Disorder

Abstract: The etiology of ADHD encompasses genetic and environmental factors. Pre-, peri-, and postnatal stressors are environmental factors that may play a role in its etiology. Future research should carefully examine interactions between genetic predisposition and environmental factors as etiologies of ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 47 publications
0
14
0
3
Order By: Relevance
“…27 Variables that were considered to have a biologically plausible effect on the risk for childhood psychopathology and in other studies have been reported as risk factors for hyperkinetic disorder were considered potential confounders in the analyses. We therefore included information on history of psychiatric hospitalizations and contact as outpatients of the mother, the father, and the siblings of the cases and control subjects, and the variables are presented in Tables 1 and 2. [14][15][16][17][18] First, the potential confounding factors were included 1 at the time. When they changed the estimate of the association between maternal smoking and hyperkinetic disorder Ͼ10%, they remained in the model.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Variables that were considered to have a biologically plausible effect on the risk for childhood psychopathology and in other studies have been reported as risk factors for hyperkinetic disorder were considered potential confounders in the analyses. We therefore included information on history of psychiatric hospitalizations and contact as outpatients of the mother, the father, and the siblings of the cases and control subjects, and the variables are presented in Tables 1 and 2. [14][15][16][17][18] First, the potential confounding factors were included 1 at the time. When they changed the estimate of the association between maternal smoking and hyperkinetic disorder Ͼ10%, they remained in the model.…”
Section: Statisticsmentioning
confidence: 99%
“…13 Nicotinic receptors are present in the fetal brain from the first trimester and play an important role in the development of the brain. 12,13 As in any complex disorder, genetic and environmental factors, 14 toxins, pregnancy and delivery complications, [15][16][17] and social environment 18 must be considered in studies of behavioral disorders. Our aim was to study the association between maternal smoking during pregnancy and the risk for hyperkinetic disorder in the offspring.…”
mentioning
confidence: 99%
“…Por outro lado, as complicações durante o parto (i.e., toxemia, eclampsia, má saúde materna, idade materna, pós-maturidade fetal, a duração do trabalho de parto, baixo peso à nascença e hemorragia pré-parto) parecem ser elementos importantes na predisposição para PHDA (Halmøy, Klungsøyr, Skjaerven, & Haavik, 2012;Ketzer, Gallois, Martinez, Ronde, & Schmitz, 2012;Sprich-Buckminster, Biederman, Milberger, Faraone, & Lehman, 1993;Zappitelli, Pinto, & Grizenko, 2001).…”
Section: Outros Fatores Etiológicos Com Origem Pré Peri E Pós-natalunclassified
“…1). The core deficit of ADHD is thought to be behavioral disinhibition (Barkley, 1997), which is largely caused by genetics (Silberg, Rutter, & Meyer, 1996) and biological influences including prenatal and perinatal complications (e.g., Sprich-Buckminster, Biederman, Milberger, Faraone, & Lehman, 1993;Zappitelli, Pinto, & Grizenko, 2001). ODD is thought to develop when largely biologically determined early child characteristics elicit and interact with family stressors and parenting practices, in a dynamic process that continues and progresses over time (e.g., Dodge & Petit, 2003;Lahey & Loeber, 1994;Lahey & Waldman, 2003;Moffitt, 1993;Patterson, 1992).…”
Section: Comorbidity Between Adhd and Oddmentioning
confidence: 99%
“…A variety of complications have been linked to ADHD and/or ODD, including cigarette and alcohol use during pregnancy, hypoxia, prematurity/low birth weight, maternal emotional and physical health during pregnancy, duration of labor, and use of forceps during delivery (Allen, Lewinsohn, & Seeley, 1998;Hartsough & Lambert, 1985;Sprich-Buckminster et al, 1993;Zappitelli et al, 2001). However, only a handful of studies have linked prenatal complications to behavior problems in preschoolaged children (Orlebeke, Knol, & Verhulst, 1999;Wakschlag & Keenan, 2001).…”
Section: The Present Studymentioning
confidence: 99%